Editorial - Fraga, Maria de Nazaré de Oliveira (Rev Rene, 2002)
What we pursue these few years of work, striving for seriousness, ethics and believing in success despite adversity, begins to materialize. The combination of these three factors and other more favored the first indexing of the journal. We want to communicate formally to our subscribers, authors and institutional partners that the Rev. RENE is included in CUIDEN database member of the Fundación Index.